Green criminology: Critical, interdisciplinary and generally welcoming to newcomers - Vaclav Walach; Petr Kupka (Sortuz)
This interview introduces green criminology as a vital approach to the study of crime, victimization and its control. It brings together two established scholars, Anna Di Ronco and Nigel South, who share their views on a range of topics, from personal reasons for engaging in green criminology and its position of green criminology in mainstream and critical criminology, to the different forms of green criminology (political economy versus cultural approaches), and possible solutions to green crimes and harms. The interview concludes with their thoughts on the public role of criminologists today.